Forgiveness Sebagai Strategi Coping Terhadap Luka Relasi Orang Tua Pada Dewasa Awal - Wati, Sindi; Sholichatun, Yulia; Rahayu, Iin Tri; Hidayati, Fina (Jurnal Ragam Pengabdian, 2026)
This study aims to explore forgiveness as a coping strategy for relational wounds with parents among emerging adults. This study employed a qualitative approach with a phenomenological design to understand participants' subjective experiences in making meaning of painful relationships with their parents. The research participants consisted of three emerging adults selected using a purposive sampling technique. Data were collected through semi-structured interviews and analyzed using Reflexive Thematic Analysis developed by Braun and Clarke (2006) and further clarified in their 2019 work. The results of the study revealed five major themes: relational wounds with parents, distress experiences resulting from relational wounds with parents, efforts to cope with relational wounds with parents, the process of meaning reconstruction toward the experience of the relationship with parents, and forgiveness as a coping strategy toward relational wounds with parents. These findings indicate that forgiveness does not occur instantly, but rather develops through a gradual psychological process, beginning with the experience of distress, survival efforts, self-reflection, and ultimately acceptance of past experiences. Accordingly, forgiveness can be understood as an adaptive coping strategy that helps individuals release emotional burdens and attain psychological calm.